56‐4: A Design of High‐Performance Touch Sensor Pattern for OLED On‐cell Structure - Nagata, Kosuke; Hata, Masayuki; Miyazaki, Shinichi; Mayumi, Masashi; Kira, Takatoshi; Noma, Mikihiro; Tanaka, Tetsunori; Kanzaki, Yosuke (SID International Symposium Digest of technical papers, 2024)
We describe an OLED on‐cell structure touch panel, which is indispensable for flexible and foldable devices. Our unique sensor pattern design has realized high signal without affecting the reflection appearance. The signal is three times higher than that of conventional patterns, making it easy to tune and realize flexible and foldable devices with high operability.